تحليل الأسلوب السردي في روايات فؤاد قنديل: (دراسة فنية) : Analysis of the Narrative Style in Fouad Qandil's Novels (An Artistic Study) - Dr. Samiya Kausar, (Al Manhal Research Journal, 2025)
The novel is a comprehensive and immersive prose narrative that explores the lives of fictional or realistic characters and events through a sequential storyline. As the largest and most expansive narrative genre, novels boast considerable scope, diverse characterizations and a vast array of events. Originating in 18th-century Europe, the novel has evolved into a highly influential and enduring literary genre. Key elements that define the fictional novel include dialogue and conflict between characters, crisis implications, plot development, narrative point of view, setting and thematic resonance. The social novel is a literary genre that explores the complexities of human behavior within societal contexts, reflecting on the values and norms that shape individual characters and communities. These novels often engage with pressing social issues of their time, including: Religion and its impact on society, Gender roles and inequalities, Racial tensions and discrimination, Social class divisions and economic disparities, Racism and xenophobia. Social novels may also delve into more intricate topics, such as: Labour rights and exploitation, Unemployment and economic instability, Poverty and income inequality, Slavery and human trafficking, Violence against women and children, Child labour and exploitation, Crime and social justice, Family dynamics and relationships, Marriage, love and partnerships, Rural and urban life, Education and illiteracy, Ignorance, bribery and corruption.